Perception as Beholding: Theological Possibility and Moral Implication of Merleau-Ponty's Notion of Embodied Subject. - TOTANES, ERICKSON L. (Budhi, 2024)
In this article, I argue that Merleau -Ponty's concept of perception reveals a way of seeing where the subject is involved with the object in a dynamic, reversible, and expanding relationship. This notion challenges the traditional and Cartesian subject -object dichotomy by emphasizing the embodied and lived experience of perception which elicits a process, a way of looking, anticipating, and reflexively, a way of being itself. By aligning seeing with beholding, I attempt to show how as simple an act as seein g evokes a manner of being related to an object, other people, and the world. The emergence of knowledge, of reality and viability of moral questions is neither the exclusive initiative of the senses or of the mind in the inside, nor of the thing known fro m the outside, but of their inseparable and intertwining relationship opened by perception itself. By this mystery which draws capacities and elements unto itself, I also show how in the process of transposing the concept of perception into beholding, Merleau-Ponty implicitly does a theology.